(untitled) (Research, Society and Development, 2021)
Periodontal health and restorative procedures are closely related and need to be in harmony. The treatment only presents a good prognosis when mechanical, biological and esthetic aspects are respected. The biological space has the function of protecting the dental element support tissues against bacterial aggression and its toxins, and its preservation is essential for proper rehabilitation. Periodontal surgery involving detachment of a full flap, osteotomy and osteoplastic are contraindicated in some cases due to compromised esthetics. Thus, orthodontic extrusion combined with fibrotomy is a treatment possibility, especially when it involves the anterior region of the maxilla. The purpose of this article is to report and discuss a clinical case of an upper incisors coronoradicular fracture with invasion of the biological space. The case had a multidisciplinary approach and planning according to the patient’s socioeconomic status, with a view to subsequent prosthetic rehabilitation. First, endodontic treatment was performed, intraradicular retention with fiberglass pins and temporary crowns. Subsequently, orthodontic root extrusion was performed using acetate plates and orthodontic elastics to re-establish the biological space. With adequate planning and performance of the correct technique it was possible to provide a subsequent favorable prosthetic rehabilitation with good prognosis.